Determining the importance of ramp performance during BMX Supercross: Use of predictive assessments and strategies to improve performance outcomes. - Carey, A. C. (2023)
The development of bicycle motocross (BMX) racing originated in the early 1970s to become a popular action sport with participation across the world. With similarity to other sprint-based and short duration cycling sports, BMX racing consists of a number of qualification races in order to make the final, with the number of races dependent upon the number of entries. The inclusion of BMX in the Olympics led the governing body, the Union Cyclist International (UCI), to develop specific criteria to showcase BMX racing at the Olympics, including qualification processes and BMX track specifications. BMX Supercross was then a series developed over the time from the Olympic inclusion announcement to the 2008 Olympic Games in Beijing, China. Further, UCI created a series of events including the World Cupseries, completed around the world in order to attain Olympic selection for countries wishing to participate.